Ayat Alkitab dan Kepatuhan Wajib Pajak Umat Katolik: Pendekatan Kualitatif dengan Theory of Planned Behavior - Wardani, Dewi Kusuma; Kusumaningrum, Maria Herawati (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to analyze the influence of biblical verses on tax compliance among Catholic taxpayers. A qualitative approach was employed using primary data collected through in-depth interviews with priests and friars as key informants, as well as parish members and church staff in Tulungagung. The findings indicate that biblical verses understood by Catholic believers contain two domains of obligation, namely obligations to God and to the state, which serve as moral foundations in interpreting tax compliance. Although the Gospel verses have diverse narrative contexts, their core teachings on obligation remain consistent. Awareness of tax compliance is not solely derived from religious understanding but is also strengthened by individual willingness and internal motivation. From the perspective of the Theory of Planned Behavior, biblical verses contribute to shaping attitudes and strengthening intentions to comply. The novelty of this study lies in its qualitative examination of tax compliance among Catholic taxpayers based on biblical values.